Thin Perforator Flaps for Reconstruction of the Lower Extremity - Ebner, Peggy J.; Gould, Daniel J.; Patel, Ketan M. (Journal of Reconstructive Microsurgery, 2019)
Thin flaps, a modification of traditional flaps that minimize the need for debulking and revision, offer unique advantages in the field of lower limb reconstruction. Advances in the field of microsurgery have made this streamlined method of reconstruction a viable solution for soft tissue coverage in patients with both trauma and nonhealing wounds. Better understanding of anatomy has allowed for flap harvest above the fascia level and the Scarpal plane. These modifications allow for flap transfer with thicknesses more comparable to the native anatomy of the lower leg, ankle, and foot. Flap survival is comparable to traditional techniques with greater potential for improved patient-centered outcomes.
Keywords: thin flap; free tissue transfer; lower extremity; microsurgery; reconstruction